Urgency of Post-issuance Supervision of Environmental Approval for Risk Activities - Tri Mulyani; Dewi Tuti Muryati; Dharu Triasih; Advento Jeronimo (Universitas Muhammadiyah Surabaya, 2024)
Every human being has the right to live in a healthy and clean and healthy environment. The state guarantees this right in the state constitution. Starting from this, the purpose of this research is to find out and analyze the urgency of post-issuance supervision of environmental approval for risky business activities in Semarang Regency. The research method used in this research is juridical sociological, with descriptive analysis specifications. The data used is primary data and supported by secondary data with qualitative data analysis method. The results show that there is an urgency for post-issuance supervision of environmental approvals for risky business activities in Semarang Regency, carried out by the Semarang Regency Regional Environmental Supervisory Officer in 2022, considering that 56 (fifty-six) out of 94 (ninety-four) responsible persons for businesses and/or activities have committed violations, namely developing business activities that do not adjust the permit. The bigger the business, the greater the impact of environmental pollution and damage, so supervision becomes very urgent to avoid greater risks.